Enhanced Replication of Highly Pathogenic Influenza A(H7N9) Virus in Humans - Yamayoshi, Seiya; Kiso, Maki; Yasuhara, Atsuhiro; Ito, Mutsumi; Shu, Yuelong; Kawaoka, Yoshihiro (Emerging infectious diseases, 2018)
To clarify the threat posed by emergence of highly pathogenic influenza A(H7N9) virus infection among humans, we characterized the viral polymerase complex. Polymerase basic 2-482R, polymerase basic 2-588V, and polymerase acidic-497R individually or additively enhanced virus polymerase activity, indicating that multiple replication-enhancing mutations in 1 isolate may contribute to virulence.